An overview of Brucellosis. - Haque, N; Bari, MS; Hossain, MA; Muhammad, N; Ahmed, S; Rahman, A; Hoque, SM; Islam, A (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):742-7 The abstract of this article is available on the PubMed website